Kepemimpinan Inovatif di Sekolah Dasar: Strategi Menghadapi Pembelajaran Modern di SD Negeri 1 Muneng - Rosidha, Laela; Sulton, Sulton (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to describe and analyze the forms and strategies of innovative leadership implemented by the principal in responding to modern learning challenges at SD Negeri 1 Muneng. The background of this research is rooted in the paradigm shift in education that requires school principals to be adaptive to technological advancements, the Merdeka Belajar (Independent Learning) policy, and the professional development needs of teachers in the digital era. This study employed a qualitative descriptive approach, with data collected through in-depth interviews, observations, and document studies. Data were analyzed using the interactive analysis model by Miles, Huberman, and Saldaña (2014), which includes the stages of data reduction, data display, and conclusion drawing. The findings reveal that the innovative leadership of the principal at SD Negeri 1 Muneng is manifested through three main dimensions: (1) transformational leadership, which emphasizes a vision for change and teacher empowerment; (2) digital competence, which supports the integration of technology into learning and school management; and (3) collaborative culture, which encourages teamwork among teachers and fosters a sustainable learning community. These three dimensions collectively form an adaptive and innovation-oriented leadership model that enhances the quality of learning in primary education